Fatigue life assessment of steel samples under various irregular multiaxial loading spectra by means of two energy-based critical plane damage models. (March 2016) - Ahmadzadeh, G.R.; Varvani-Farahani, A.
Highlights: Fatigue lives of steel alloys for multiaxial irregular loading paths are predicted. Energy based damage models of Varvani and Łagoda–Macha have been employed. Cycle-counting of Wang–Brown is applied to count reversals over loading spectra. The choice of damage models is discussed based on accuracy in damage assessment. Abstract: Fatigue life of different steel alloys undergoing multiaxial irregular loading spectra was evaluated based on two energy-based models of Łagoda–Macha (LM) and Varvani-Farahani. The LM damage model evaluated the life of samples from calculation of the equivalent strain energy densities over counted reversals of the applied stress and strain histories on the critical plane. The Varvani damage approach assessed fatigue life through integration of the normal and shear energy ranges calculated on the critical plane at which the largest stress and strain Mohr's circles over the counted loading and unloading reversals were determined. Based on the equivalent relative strain method of the Wang–Brown, peaks and valleys (reversals) were counted over irregular multiaxial loading spectra. Damage values were calculated and then accumulated over peak–valley events of a block loading spectrum. The overall damage over block histories was then related to fatigue life Nf in the right hand side of the damage models. The predicted lives based on these damage models were compared with those of reported experimental data. The choice of damage assessment models and how to determine the fatigue life of components under irregular loading spectra were discussed.